STRATEGI MANAJEMEN SUMBER DAYA MANUSIA MENDUKUNG TRANSFORMASI DIGITAL PELAYANAN KESEHATAN DI RSU PENGAYOMAN CIPINANG - Sofia Wahyutiningrum; Alih Aji Nugroho (Journal of Contemporary Public Administration, 2025)
The digital transformation of healthcare services in Indonesia faces fundamental challenges related to human resource (HR) readiness, particularly in vertical hospitals under non-health ministries, which operate with distinct bureaucratic complexities and budgetary constraints compared to hospital under the Ministry of Health. This study aims to formulate human resource management strategies to support the digital transformation of healthcare services at RSU Pengayoman  Cipinang, with a focus on optimizing the role of healthcare workers as primary users of digital systems. A descriptive qualitative method with a case study was employed over three-month period from August to October 2025, involving 14 informants selected through purposive sampling.These  informants included hospital leadership, IT coordinators, medical records  coordinators, nursing coordinators and healthcare personnel across various service units.  Data collection was conducted through in-dept interviews, participatory observation of the use of SIMRS, Electronic Medical Records (EMR), and Telemedicine across units, as well as document analysis of monthly reports and internal policies. Data were analyzed using thematic analysis and triangulation techniques to ensure the validity of finding. The study revealed a paradoxical phenomenon : although SIMRS utilization reached 90,10%, compliance in EMR data entry, specifically SOAP notes rose from 49% to 98%, and ICD-10 coding from 40% to 84% between March and August 2025 following intensive mentoring. However, complex categories at 22%. The findings indentified four significant Hr related factors: (1) uneven digital competence (80-85%) of staff capable of basic operations but lacking proficiency in complex documentation.,(2) healthcare worker performance hindered by limited computer to staff ratios,(3) insufficient IT team capacity, and (4) a transformation leadership style not yet supported by an adequate evaluation system. The novelty of this research lies in its integrative approach, combining Strategic Human Resources Management (SHRM) theory with the POAC management functions, adapted to the unique context of correctional hospitals. This approach produced a comprehensive strategic model encompassing tired and structured digital training, development of systems and performance -based monitoring mechanisms relevant to vertical hospitals under no_health ministries.